Green Ekonomi Sebagai Dasar dalam Pengambilan Keputusan Pengendalian Persediaan Bahan Baku Industri Kreatif Perspektif Ekonomi Islam - Rosida, Ika Nazilatur (Journal of Industrial and Syariah Economics, 2025)
The green economy is a concept that supports human welfare and cares about both the sustainability of the environment and the ecosystems in economic development. To grow economic welfare, society produces written and hand-woven Batik Gedog in the creative industry. The production process requires the main raw materials that are from natural products, so effort is needed to keep the survival of plants from becoming extinct and return to green.  This research is qualitative and uses a descriptive analysis approach. The purpose of this research is to analyze the green economy as the basis for making decisions in the control of the raw materials inventory in the creative industry of written and hand-woven Batik Gedog Sekar Ayu Wilujeng Kedungharjo, Kerek Tuban. The data was obtained through interviews and documentation. The results of the research show that the creative industry of written and hand-woven Batik Gedog Sekar Ayu Wilujeng implements a green economy through conservation and replanting Brown Silk-cotton Tree, natural dyes of Indigo, Soga, and Tunjung wood prevent extinction. It’s consistent with Islamic teachings and the Islamic economic goal, with sustainability, production can be maintained, and the economic welfare of creative industrial actors can be achieved.